2020
DOI: 10.3390/biomedicines8020038
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Oral Administration of LLHK, LHK, and HK Alters Gene Expression Profile and Restores Age-Dependent Atrophy and Dysfunction of Rat Salivary Glands

Abstract: Xerostomia, also known as dry mouth, is caused by a reduction in salivary secretion and by changes in the composition of saliva associated with the malfunction of salivary glands. Xerostomia decreases quality of life. In the present study, we investigated the effects of peptides derived from β-lactoglobulin C on age-dependent atrophy, gene expression profiles, and the dysfunction of salivary glands. Long-term oral administration of Leu57-Leu58-His59-Lys60 (LLHK), Leu58-His59-Lys60 (LHK) and His59-Lys60 (HK) pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…As previously mentioned, oral administration of LHK upregulates proline-rich protein genes (Prpmp5, Prb3, Prp2, Prb1, Prp15), cystatin genes (Cst5, Cyss, Vegp2), amylase genes (Amy1a, Amy2a3), and lysozyme gene (Lyzl1), and AP-2 transcription factor gene (Tcfap2b) (15). The administration of LLHK, LHK, and HTK prevents and / or restores the age-dependent atrophy and functional decline of salivary glands.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…As previously mentioned, oral administration of LHK upregulates proline-rich protein genes (Prpmp5, Prb3, Prp2, Prb1, Prp15), cystatin genes (Cst5, Cyss, Vegp2), amylase genes (Amy1a, Amy2a3), and lysozyme gene (Lyzl1), and AP-2 transcription factor gene (Tcfap2b) (15). The administration of LLHK, LHK, and HTK prevents and / or restores the age-dependent atrophy and functional decline of salivary glands.…”
Section: Discussionmentioning
confidence: 87%
“…Previously, we reported that the administration of whey from Jersey cow milk mitigates age-dependent atrophy and functional decline of salivary glands accompanied with changes in gene expression in rats (12). We found that the bioactive peptides, which were LLHK, LHK, and HK derived from β-lactoglobulin C variant, prevent and / or restore the age-depending decline in structure and function of salivary gland (15). In those experiments, older rats drank the whey or the peptides.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations